Research and Discussion of Operator's Strategy in the Mobile Internet Era - Shuo Mao (Dianxin kexue, 2014)
The development of mobile internet caused the significant changes of mobile communication industry and advanced the integration of mobile communication, internet and media industries. In this progress, mobile operators had the marginalization and channelization risks. To help mobile operators cope with the challenges, the main characteristics of the industry was researched and the challenges of mobile operators in the application field were closely analyzed. Five strategies, such as optimizing basic network, constructing core competitive power in content and application fields etc, were put forward to create mobile operators' value in the change of industry.